2007
DOI: 10.1002/jso.20772
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognostic values of lymph node metastasis in operable hepatocellular carcinoma and evaluation of routine complete lymphadenectomy

Abstract: The incidence of LNM in operable HCC patients was low, and patients with LNM had a poorer prognosis. LNM status determined the disease-free survival but not the overall survival of HCC. The complete lymphadenectomy did not improve overall survival, as compared with chemotherapy or radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 24 publications
1
67
2
1
Order By: Relevance
“…3,4,6,9 Although the incidence of lymph node metastasis (LNM) in operable HCC is as low as 1.7% to 7.5%, 10,11 lymph node (LN) status is a definite prognostic factor in HCC and leads to generally dismal survival rates. 11,12 In our previous report we found that the development of LNM was related to higher T classification. 12 Furthermore, Uenishi et al 3 found that patients with HCC with CK19 expression had LNM.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…3,4,6,9 Although the incidence of lymph node metastasis (LNM) in operable HCC is as low as 1.7% to 7.5%, 10,11 lymph node (LN) status is a definite prognostic factor in HCC and leads to generally dismal survival rates. 11,12 In our previous report we found that the development of LNM was related to higher T classification. 12 Furthermore, Uenishi et al 3 found that patients with HCC with CK19 expression had LNM.…”
mentioning
confidence: 87%
“…11,12 In our previous report we found that the development of LNM was related to higher T classification. 12 Furthermore, Uenishi et al 3 found that patients with HCC with CK19 expression had LNM. Likewise, we postulated that HCC with LNM can also be classified by the presence of CK19 expression, namely, positive with ICC-like differentiation and negative with higher T classification.…”
mentioning
confidence: 87%
See 3 more Smart Citations